Meta-QTL Analysis in Rice and Cross-Genome Talk of the Genomic Regions Controlling Nitrogen Use Efficiency in Cereal Crops Revealing Phylogenetic Relationship - Sandhu, Nitika; Pruthi, Gomsie; Prakash Raigar, Om; Singh, Mohini Prabha; Phagna, Kanika; Kumar, Aman; Sethi, Mehak; Singh, Jasneet; Ade, Pooja Ankush; Saini, Dinesh Kumar (Frontiers in Genetics, 2021)
The phenomenal increase in the use of nitrogenous fertilizers coupled with the poor nitrogen use efficiency are among the most important threats to the environment, economic and social health. During the last two decades, a number of genomic region associated with nitrogen use efficiency (NUE) and related traits have been reported by different research groups but none of the stable and major effect QTL have been utilized in marker-assisted introgression/pyramiding program. Compiling the data available in literature could be very useful in identifying stable and major effect genomic regions associated with root and NUE related trait improving rice grain yield. In the present study, we performed meta-QTL analysis on 1,330 QTL from 29 studies published in past two decades. A total of 76 MQTL with stable effect over different genetic backgrounds and environments were identified. The significant reduction in the confidence interval of the MQTL compared to the initial QTL resulted in the identification of annotated and putative candidate genes related to the traits considered in the present study. Hot spot region associated with correlated traits on chr 1, 4 and 8 and candidate gene associated with nitrate transporters, nitrogen content and ammonium uptake on chromosome 2, 4, 6 and 8 have been identified. The identified MQTL, putative candidate genes and their orthologues were validated on our previous studies conducted on rice and wheat. The research-based interventions such as improving nitrogen use efficiency via identification of major genomic regions and candidate genes can be plausible simple and low-cost solution to address the challenges of crop improvement program.